The Frequency of Prescribing Nonsteroidal Anti-inflammatory Drugs in a Public Hospital - Ahmed, Mr. Nehad J. (Asian Journal of Pharmaceutics (AJP), 2021)
Aim: This study aims to explore the frequency of prescribing nonsteroidal anti-inflammatory drugs (NSAIDs) in a public hospital in Al-Kharj. Materials and Methods: This study included review the electronic medical records of outpatients who received at least one of the NSAIDs between January 1, 2018, and June 30, 2018, in a public hospital in Al-Kharj. Results: The most commonly prescribe NSAIDs was diclofenac (61.23%) followed by ibuprofen (36.12%). About half of the patients receiving NSAIDs were <30 years old (50.17%) and about 72.25% of them were <40 years old. Only diclofenac was prescribed as a topical form (gel, cream, or ointment). More than 71% of diclofenac prescriptions were included a topical dosage form. Conclusion: The study showed that nonaspirin NSAIDs prescribing rate was high, particularly diclofenac and ibuprofen. It is important to increase the awareness of health-care providers to increase the efficacy and decrease the adverse effects of these medications.